2017
DOI: 10.17691/stm2017.9.4.06
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Elastography: Comparing the Accuracy of Ultrasound Scanners Using Calibrated Phantoms in Experiment

Abstract: The aim of the study was to compare the accuracy of shear wave elastography performed by ultrasonic scanners from different manufacturers and to develop the conversion coefficients to recalculate the stiffness values obtained with different instruments using a calibrated phantom. Materials and Methods. A comparative analysis of the accuracy of stiffness measurements by shear wave point elastography was performed using three commercial ultrasonic scanners: Aixplorer (Supersonic Imagine, France), Acuson S2000 (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 6 publications
3
10
0
Order By: Relevance
“…Our results support the consensus in the literature that SWE measurements can be considerably different between different machines [ 11 , 13 , 15 , 17 , 19 , 27 , 30 ]. For example, Shin et al [ 19 ] investigated three machines (Aixplorer, ACUSON S3000, and EPIQ 5) and reported inconsistent measurements using curved probes at various depths between 2 cm and 5 cm.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results support the consensus in the literature that SWE measurements can be considerably different between different machines [ 11 , 13 , 15 , 17 , 19 , 27 , 30 ]. For example, Shin et al [ 19 ] investigated three machines (Aixplorer, ACUSON S3000, and EPIQ 5) and reported inconsistent measurements using curved probes at various depths between 2 cm and 5 cm.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of measurement bias, our results suggest a significant difference, ranging on average from 16% to 48%, between the measured SWE values and the theoretical values provided by the phantom manufacturer. This finding is consistent across the majority of studies conducted on CIRS phantoms [ 11 , 12 , 14 , 15 , 17 - 21 ]. The only exception was the study of Mulabecirovic et al [ 13 ], who used the 049 model and reported accurate measurements using the GE machine (9L-D probe) and SSI machine (probe 2).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results may differ if patients move between healthcare institutions employing alternative ultrasound systems; therefore, clinical decision-makers must consider this during clinical practice. Conversion formulae have been suggested to adapt the measurements between ultrasound systems to aid comparability [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several ultrasound systems on the market. Much of the technology and mechanisms behind SWE are patented and, therefore, inaccessible to researchers and clinicians [ 3 ]. However, only a few studies have explored the inter-system accuracy and reliability of different ultrasound systems [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%